Comparison of Objectivity in US Alternative Media and Mainstream Media Websites' Hard News Articles Using the Appraisal Framework - Lehtonen, Pipariina (fi=Turun yliopisto|en=University of Turku|, 2018)
The topic of this thesis is the comparison between the objectivity of alternative media and mainstream media websites’ hard news articles in the United States. It aims to discover the types of subjectivities occurring in the two types of media, the similarities and/or differences in these ways of subjectivity shown, as well as the possible reasons for these similarities and/or differences. The data for the study consists of 12 articles from four different websites: CNN and New York Times representing mainstream media and Breitbart News Network and Truthout representing alternative media. Three articles that have to do with the same three controversial topics were chosen from each website to be included in the data. The data is analysed with the use of the appraisal framework, mainly its devices of attitude and attribution. The attitudinal expressions and attributions in the two data are counted and further divided into subcategories: attitudes into affects, judgements, and appreciations, while attributions are divided into acknowledgements, endorsements and distancings. The polarities of the attitudes expressed are also examined and compared between the mainstream and alternative media results, as well as the frequencies of each subcategory of attitudes and attributions, and finally, the possible reasons for the similarities and differences are discussed. The results were found to be fairly similar in the two data: all types of attitudes and attributions were found in both sets of data and the distributions of the subcategories of attitudes and attributions were very close to each other. However, there were also a few differences: while there were overall more attitudes and attributions in the mainstream media articles, the alternative media articles tended to be somewhat more negative and used more attributions expressing marked stance. As for the reasons for these similarities and differences, a few possible ones were discussed: the mainstream media news organisations are bigger and more popular than the alternative media ones, which means they probably have more access to people to interview in their news reports, which in turn increases the number of attributions. This larger amount of external voices used in the mainstream media might also be the reason for the larger number of attitudes expressed. The similarities, however, might be due to the two types of media being from the same country and the same culture, using the same language and discussing the same topics.